The Adoption of New Smart-Grid Technologies Incentives, Outcomes, and Opportunities - Guo, Christopher (RAND Corporation, 2015)
RAND Corporation researchers review the current technical, regulatory, and economic context of the electricity market and theoretical benefits of developing a smart grid; discuss some entrepreneurial opportunities associated with smart-grid data; examine empirical evidence related to smart-grid adoption and implementation; and offer policy suggestions for overcoming identified barriers.